Mannheim’s Problem of Generations as a Phenomenon of Cultural Change (KULT_online, 2009)
Beate Fietze's monograph applies a sociological perspective to historical generations and their relation to social change. She is therefore active in the sociology of generations, a field dominated by Karl Mannheim’s theories, and points to the relevance of generation-theory for processes of social change. In doing so, Fietze puts her finger on a very up-to-date topic that has been continuously gaining importance in Germany since the 1980s. She analyses different approaches to generation-theories that mainly go back to Mannheim and develops them further to make them available to research in conjunction with the study of culture.